Cifte Amam 2. - Milevska, Suzana; Pirkoska, Koncha (Skopje : SCCA (Soros Center for Contemporary Arts), 1996)
Avramovska, Elizabeta ; Arsovska, Mirna ; Atanasoski, Atanas ; Adzigogova, Svetlana Korunovska ; Baseski, Zarko ; Blazeska, Violeta ; Grabuloski, Bogdan ; Slatinec, Katerina Madzar ; Dimitrova, Iskra ; Gligorov, Zlatko ; Guzelova, Liljana ; Jankuloski, Robert ; Kalajdzieva, Margarita Kiselicka ; Maznevski, Antoni ; Moteska, Monika ; Pavleski, Stanko ; Radevska, Dljana Tornic ; Ramicevic, Ismet ; Svetieva, Aneta ; Sokolovski, Slavco ; Spasovic, Dejan ; Suki, Miroslav Stojanovic - ; Trajkovski-Hinki, Zlatko ; Uzunovski, Simon ; Urosevic, Vana ; Pecov, Hapez - Zlatko Hadzi
biografie
Cifte Amam 2, Cifte Amam - Old Bazaar, Skopje, 10-20.05.1996
Engels & Macedonisch
boek